Native oesophageal mucocoele: A rare complication of double exclusion of oesophagus. (November 2021) - Jena, Suvendu Sekhar; Obili, Ravi Chandra Reddy; Yadav, Amitabh; Das, Sri Aurobindo Prasad; Nundy, Samiran
Abstract: Introduction and importance: Native oesophageal mucocoele usually follows bipolar exclusion of oesophagus for various reasons and is very rare in literature. Though mostly asymptomatic, its symptoms can be divided into 3 groups – Compressive, Infective and fistulizing symptoms. The management options described in the literature are percutaneous drainage, chemical ablation, esophagectomy and internal drainage using Roux-en-Y reconstruction. Case report: A 40 year old female, presented with complaints of dysphagia, weight loss and chest pain for 6 month. She had history of retrosternal gastric pull-up for oesophageal stricture following corrosive injury. On evaluation with CT chest, there was a well-defined fluid attenuated tubular elongated lesion in the mediastinum in the region of oesophagus which was non-opacified with oral contrast and a diagnosis of giant oesophageal mucocoele was made. She underwent internal drainage of mucocoele by roux-en-Y esophagojejunostomy with placement of transanastomotic drain and discharged with an uneventful recovery with the trans-anastomotic drain in situ, which was removed on outpatient basis. Now she is asymptomatic in the subsequent follow up. Clinical discussion and conclusion: Though rare, mucocoele of oesophagus can lead to life threatening complication like respiratory distress, sepsis. Its diagnosis requires high index of suspicion and CT chest is helpful. Management options depend upon nutritional status of the patient and associated co-morbidities. Esophagectomy is the definitive form of treatment but not always possible and other options can be internal or percutaneous drainage. Highlights: Native esophageal mucocele usually follows bipolar exclusion of esophagus for various reasons. Usually asymptomatic, but can have three types of presentation with compressive, infective and fistulizing symptoms. When sufficiently large, it causes compressive symptoms which includes life threatening respiratory distress due to compression of the tracheobronchial tree, septic complications and fistulization. Various treatment options are available, like percutaneous aspiration with chemical ablation, resection of the mucocoele or rarely, internal drainage using a Roux en Y reconstruction.